Production and examination of oxygen‐carrier materials based on manganese ores and Ca(OH)2 in chemical looping with oxygen uncoupling. Issue 2 (9th November 2013) - Pour, Nasim M.; Azimi, Golnar; Leion, Henrik; Rydén, Magnus; Lyngfelt, Anders
<x xml:space="preserve">Abstract</x> This study concerns production of oxygen‐carrier particles using six different manganese ores. The ores were made to react with Ca(OH)2 at elevated temperature, forming calcium manganite. The method utilized to manufacture particles was extrusion. Methane and syngas conversion and oxygen release of the samples in inert atmosphere were investigated. The oxygen carrier based on South African (B) manganese ore, showed good methane conversion and was able to transfer oxygen corresponding to 1.5% of its mass during reduction with gaseous fuel. All examined oxygen carriers were capable of converting syngas completely. The ability to release gaseous oxygen was examined by adding wood char in a stream of nitrogen for four selected samples sintered at 1300°C/6 h. These samples released an amount of oxygen corresponding to 0.37–0.68% of their mass. The reactivity of all the ores was improved after the proposed treatments. Reactivity results of the oxygen carrier made from South African (B) ore and Ca(OH)2, sintered at 1300°C for 6 h were the most promising. Attrition measurements with a jet cup of the oxygen carriers sintered at 1300°C/6 h showed that all the samples made from ores were at least three times more resistant to mechanical attrition compared to particles made from synthetic Mn2O3. Producing feasible oxygen carriers directly from ores could potentially cut the cost of chemical looping with oxygen uncoupling and have a significant impact on its competitiveness among other carbon capture technologies. © 2013 American Institute of Chemical Engineers AIChE J 60: 645–656, 2014